Increase of Accuracy of the Fault Location Methods for Overhead Electrical Power Lines - Vladimir Lebedev; Galina Filatova; Alexander Timofeev (Advances in Materials Science and Engineering)
The high-voltage power lines are quite often damaged parts of the energy system. Line outage is always accompanied by undersupply of energy and decrease of reliability, cost, and quality of electric supply. That is why one of the important tasks of line maintenance is quick looking for location of the damage and organization of the rehabilitation. The main part of this work includes development and research of the methods and algorithms for fault location based on one-sided measurement and the ways to increase their accuracy. This type of measurement uses signals from digital current and voltage transformers as input. The influence of the basic distorting factors on the accuracy of the fault location determination methods is also considered.